Migration of Sn and Pb from Solder Ribbon onto Ag Fingers in Field-Aged Silicon Photovoltaic Modules. (16th September 2015) - Oh, Wonwook; Kim, Seongtak; Bae, Soohyun; Park, Nochang; Chan, Sung-Il; Kang, Yoonmook; Lee, Hae-Seok; Kim, Donghwan
Abstract : We investigated the migration of Sn and Pb onto the Ag fingers of crystalline Si solar cells in photovoltaic modules aged in field for 6 years. Layers of Sn and Pb were found on the Ag fingers down to the edge of the solar cells. This phenomenon is not observed in a standard acceleration test condition for PV modules. In contrast to the acceleration test conditions, field aging subjects the PV modules to solar irradiation and moisture condensation at the interface between the solar cells and the encapsulant. The solder ribbon releases Sn and Pb via repeated galvanic corrosion and the Sn and Pb precipitate on Ag fingers due to the light-induced plating under solar irradiation.